Prediction of Preeclampsia and Other Adverse Pregnancy Outcomes in Women of Advanced Maternal Age: The Use of Mid Trimester Uterine Artery Doppler Velocimetry. - Oforma, Ngwu Hillary; Emmanuel, Olugbenga Olorungbogo; Isoken, Aikpopo; Xavier, Enodiana; Governor, Okome; Festus, Omorogbe; Anthonia, Njoku; Joseph, Eigbefoh; Theophilus, Akhigbe (British Journal of Healthcare and Medical Research, 2025)
Background: Adverse pregnancy outcomes such as pre-eclampsia, gestational diabetes, and low birth weight are significant contributors to maternal and fetal morbidity. The use of Doppler ultrasonography, particularly pulsatility index (PI) and the presence of a notch, has been explored as a predictive tool for identifying pregnancies at risk of these complications. Objectives: This study aimed to evaluate the association between uterine artery Doppler findings, specifically PI and notching, with adverse maternal and fetal outcomes among pregnant women. Methodology: A cross-sectional study was conducted among 141 pregnant women at Irrua Specialist Teaching Hospital, Nigeria. Doppler ultrasonography was used to assess PI and the presence of a notch. Participants were followed up to delivery, and data on outcomes, including pre-eclampsia, gestational diabetes, low birth weight, and pre-term delivery, were analyzed. Statistical analysis was performed using SPSS 23.0, with significance set at p < 0.05. Results: Women with abnormal PI were four times more likely to develop pre-eclampsia compared to those with normal PI. Abnormal PI was also associated with twice the risk of gestational diabetes and three times the likelihood of delivering a low-birth-weight infant. The presence of a notch was significantly associated with pre-eclampsia, doubling the risk compared to cases without a notch. However, neither abnormal PI nor notching demonstrated significant associations with caesarean section rates, ICU admission, or poor APGAR scores. Conclusion: Doppler findings, particularly abnormal PI and notching, are valuable in identifying pregnancies at risk for complications like pre-eclampsia and low birth weight. Routine integration of Doppler screening into antenatal care is recommended to enable early detection and timely interventions, thereby improving maternal and fetal outcomes.